Design of Sprinkler Irrigation for Orchids - Kurniati, Evi; Suharto, Bambang; Afrilia, Tunggal (Jurnal Teknologi Pertanian, 2007)
The export of orchids increased from about US$ 3 million in 1999 to US$ 4,1 million in 2002. An improvement in any aspects of its culture techniques is important to increase its productivity. One of the techniques need to develop is related to the irrigation system. The research was conducted to develop a sprinkle type irrigation system for Cattelya orchids of 6-7 years old, cultured in Batu, Malang. The system was then designed, constructed and tested. Â  It was found that, the daily water requirement of this particular orchid was 0.12 L. Based on the water requirement, the irrigation system was designed and constructed. At a design level, the measurements showed that the daily discharges of the sprinkle, lateral pipe and main pipe were 0.49 L, 4.88 L and 24.37 L respectively. The total head loss resulted from the sprinklers, lateral pipe, main pipe, 90ï‚° angles and joints was 2.46 x 10-4 m, at a total head of pump of 10.00024631 m. The results of the performance tests on the constructed system showed that the discharge levels were lower than that at the designed level. It was probably due to the pump efficiency which was recorded as low as 29.31%. It was found that at 25 Psi, the water sprayed diameter was 0.8 m, with the respective values of the uniformity coefficient, uniformity distribution, PELQ and AELQ were 88.76%, 57.87%, 10.53% and 8.53%. The total cost needed for the irrigation system was 4,197.22 rupiahs/m2.Key words: design, sprinkler irrigation, orchid